An investigation to improve performance of grounding system - Mohammad Shafiqul Naim, Shafie (2016)
An ideal grounding system is very important to dissipate short circuit current and to protect people from shock. Engineers often face difficulty when designing a satisfactory grounding system for building especially located at high soil resistivity. To improve the performance of grounding system, backfilled with low soil resistivity must be added in the grounding system. In this study, rice straw ashes, cow dung and oil palm husk are tested together with existing material which is bentonite. Fall of potential method is used as it’s compatible for different type of grounding medium and this study need extensive research site. Based on analysis, rice straw ashes shows 77% increase in its resistance efficiency compared to bentonite. In conclusion, Rice straw ashes have been determined as the favorable waste material to reduce earth resistance as compared to cow dung and oil palm husks.